До проблематики генезизу та дефініції економічної категорії «витрати» - Шматковська, Тетяна Олександрівна; Shmatkovska, Tetiana О.; Демедюк, Людмила Володимирівна; Рудь, Тетяна; Demediuk, Liudmyla V.; Rud, Tetiana (Одеський національний економічний університет, 2016)
The article examines the historical development of the concept of "expenses". Researched understanding of cost categories in the Ancient World: Egypt, Babylon, Greece, the Roman Empire and the birth of the features of accounting costs in these countries. A chronological analysis of phased approaches to the category of "costs". Researchers analyzed the approaches of different economic schools to factors of production value and costs. Incrementally systematized historical development category "expenses." Features emergence of cost accounting methods and the need to control costs and the emergence of management accounting as a separate science. The peculiarities of modern scientific approaches to the treatment costs. A distinction between "cost", "cost", "costs" and "payments". Presents a modern understanding of the term costs in other countries. The author researched the definition of the concept. У статті розглянуто історичний розвиток поняття «витрати». Досліджено розуміння категорії витрат у країнах Стародавнього світу: Єгипті, Вавилоні, Греції, Римській імперії та особливості зародження організації обліку витрат в цих країнах. Проведено поетапний хронологічний аналіз підходів до категорії «витрати». Проаналізовано підходи дослідників різних економічних шкіл до визначення факторів формування вартості продукції та витрат. Поетапно систематизовано історичний розвиток категорії «витрати». Розглянуто особливості виникнення методів обліку витрат, необхідність управління витратами та появи управлінського обліку як окремої науки. Висвітлено підходи сучасних вчених до трактування витрат. Проведено розмежування між «витратами», «затратами», «видатками» та «платежами». Представлено сучасне розуміння терміну «витрати» в різних країнах. Запропоновано авторське визначення досліджуваного поняття.
To the problems of the genesis and definition of economic category “expenses”
Keywords: expenses; genesis of the concept of "expenses"; opportunity expenses; economic resources; expenses management; витрати; генезис поняття «витрати»; альтернативні витрати; економічні ресурси; управління витратами